The Relationship Between Academic Self-Efficacy and Mathematics Anxiety in Upper Elementary School Students : Hubungan Antara Efikasi Diri Akademik dengan Kecemasan Matematika pada Siswa Sekolah Dasar Tingkat Atas - Shafa Safiyah; Widyastuti (Academia Open, 2022)
This study investigates the relationship between academic self-efficacy and mathematics anxiety in upper grade students of elementary schools in Sidoarjo. A total of 185 students from two schools participated in this study. The academic self-efficacy and mathematics anxiety scales were employed for data collection. Using saturated sampling analysis, a significant negative correlation coefficient of -0.248 (p < 0.001) was found, indicating a negative association between academic self-efficacy and mathematics learning outcomes. The students exhibited a moderate level of academic self-efficacy (43%) and mathematics anxiety (39%). The implications of these findings contribute to our understanding of the interplay between academic self-efficacy and mathematics anxiety among upper grade students, thereby offering valuable insights for educators, policymakers, and researchers to enhance mathematics education strategies and support mechanisms. Highlights: The study explores the relationship between academic self-efficacy and mathematics anxiety in upper grade elementary students. A negative correlation (-0.248) between academic self-efficacy and mathematics learning outcomes is observed. The findings suggest the importance of addressing mathematics anxiety and fostering academic self-efficacy to improve mathematics education for upper grade students. Keywords: Academic self-efficacy, mathematics anxiety, upper grade students, elementary school, Sidoarjo.